2010
DOI: 10.1039/b914703a
|View full text |Cite
|
Sign up to set email alerts
|

Novel AAO films and hollow nanostructures fabricated by ultra-high voltage hard anodization

Abstract: Novel anodic aluminium oxide (AAO) films and hollow nanostructures were synthesized via a simple electrochemical and chemical etching route; fluctuating nanotube growth inside AAO film fabricated under ultra-high voltage was considered to be the main reason for the formation of such new structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 25 publications
1
34
1
Order By: Relevance
“…From these results we hypothesize that the ethanol concentration-dependant breakdown effect is caused by the rapid heat generation at the bottom of the nanopores, which leads to the catastrophic local flow of current across the oxide barrier layer. EtOH has been frequently used as a coolant to achieve HA condition under high electric field conditions at temperatures below 0 C [28][29][30]. However, our result demonstrated that EtOH is not efficient to dissipate the heat generated during HA process when the temperature of the electrolyte is relatively high.…”
Section: Fabrication Of Ultra-short Aants By Modifying Electrolytecontrasting
confidence: 76%
“…From these results we hypothesize that the ethanol concentration-dependant breakdown effect is caused by the rapid heat generation at the bottom of the nanopores, which leads to the catastrophic local flow of current across the oxide barrier layer. EtOH has been frequently used as a coolant to achieve HA condition under high electric field conditions at temperatures below 0 C [28][29][30]. However, our result demonstrated that EtOH is not efficient to dissipate the heat generated during HA process when the temperature of the electrolyte is relatively high.…”
Section: Fabrication Of Ultra-short Aants By Modifying Electrolytecontrasting
confidence: 76%
“…The hard anodizing allows the fabrication of a self-ordered porous oxide with various cell diameters under high voltage conditions: sulfuric acid at 27-80 V to 72-145 nm [104], oxalic acid at 120-150 V to 220-300 nm [105], and phosphoric acid at 195 V to 320-380 nm [106]. In addition, several research groups have reported using the advanced hard anodizing technique to further extend the self-ordering voltage and the corresponding cell diameters [107][108][109][110][111]. Noh et al have reported the fabrication of highly ordered nanotubular aluminum oxide by hard anodizing [112].…”
Section: Fabrication Of Highly Ordered Porous Aluminum Oxidementioning
confidence: 99%
“…49 It worth mentioning that more Al(OH) 3 can be formed under certain anodization conditions with a higher U a . 49,52 Considering that Al(OH) 3 has a relatively small dissociation energy (3.80 kcal mol −1 ), it will dehydrate easily during high voltage anodization thus leading to volume contraction of the AAO cell walls. 16,49,52 Accordingly, it is not surprising to see that ξ decreases with U a (Figure 3).…”
Section: Resultsmentioning
confidence: 99%